2011
DOI: 10.1246/bcsj.20100348
|View full text |Cite
|
Sign up to set email alerts
|

Cladielloides C and D: Novel Eunicellin-Based Diterpenoids from an Indonesian Octocoral Cladiella sp.

Abstract: Chemical investigation on an Indonesian octocoral identified as Cladiella sp. has led to the isolation of two novel eunicellin-based diterpenoids, cladielloides C (1) and D (2). The structures of 1 and 2 were established by spectroscopic methods. Compound 1 exhibited significant cytotoxicity toward CCRF-CEM tumor cells and metabolites 1 and 2 displayed moderate inhibitory effects on superoxide anion generation by human neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Also, compounds 1 , 4 and 5 exhibited moderate to weak cytotoxicity toward CCRF-CEM and MOLT 4 cell lines. Besides our research, many recent studies have showed the versatile structures and bioactivities of eunicellin-type compounds [16,17,18,19,20,21]. These studies along with the new simplexins described here suggest that eunicellin-type compounds, in particular 3, are worthy of further biomedical investigation.…”
Section: Methodssupporting
confidence: 60%
“…Also, compounds 1 , 4 and 5 exhibited moderate to weak cytotoxicity toward CCRF-CEM and MOLT 4 cell lines. Besides our research, many recent studies have showed the versatile structures and bioactivities of eunicellin-type compounds [16,17,18,19,20,21]. These studies along with the new simplexins described here suggest that eunicellin-type compounds, in particular 3, are worthy of further biomedical investigation.…”
Section: Methodssupporting
confidence: 60%
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory evaluations in vitro showed diterpenoid 124 significant inhibits the production of superoxide anion and the release of elastase by human neutrophils with IC 50 =5.9±0.7, 6.5±1.9 μg/mL, respectively. Their continuous study on this organism afforded two novel eunicellin‐type diterpenoids, namely cladielloides C ( 125 ) and D ( 126 ) [51] . It was worth noting that the structure of 125 furnished the additional ether bridge between C‐3 and C‐6 as a part of a hemiketal constellation, and 106 was the second example of 6,7‐secoeunicellin.…”
Section: Marine Natural Products From the Genus Of Cladiellamentioning
confidence: 99%